Investigating literacy development among learners with a second language as medium of education : the effects of an emergent literacy stimulation program in Grade R - Olivier, Johanna M. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (DPhil (General Linguistics))—University of Stellenbosch, 2009.